Food choices of students with nutritional knowledge. - POPESCU-MITROI, Ionel; POPESCU-MITROI, Maria Monica (Nutrición Clínica y Dietética Hospitalaria, 2022)
Objective: This exploratory studyaims to identifyat the students who have acquired basic nutritional knowledge theoptions based of what healthy / less healthy foods mean, to what extent the conservatism / novelty is important in choosing products and how much independent / dependent their food choices are in fact. Methods: The methodology used in this paper consisted in drawing up a 38-item questionnaire by authors and its completion by 50 students who attended a nutrition course. Results: This study reveals on the following tree major lines: at the axis healthy versus unhealthy food choices there areno significant differences between the two categories (Paired samples test, t = 1.20, p = 0.235), at the axis choices based on conservatism versus novelty aresignificant results for conservatism (Paired samples test / t = 6.95, p = 0.000 )and at the axis choices based on decisional independence versus dependenceare significant results for independence (Paired samples test, t = 5.59, p = 0.000). Implication: Basically, this paper makes a clear radiography of the respondents’ food choices and it may also provide through the questionnaire developed by us a starting point for developing new information, education and marketing strategies to promote the healthy food consumption.